MENJEMBATANI GENERASI: STRATEGI KREATIF MEMPERKENALKAN BUDAYA LOKAL KEPADA KAUM MILENIAL - Arif Tri Hartanto; Fikri Ilham Fauzi (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2024)
This study analyzes the influence of packaging innovation and digital marketing strategies on the interest of the younger generation in local cultural events in Bandung. This study was motivated by the low level of participation of the younger generation in cultural activities, despite Bandung's rich cultural heritage. This study used a quantitative survey method involving 154 respondents aged 18-30 years old. Data was collected through questionnaires and analyzed using linear regression to assess the impact of creative packaging and digital marketing on the engagement of the younger generation in local culture. The results showed that packaging innovation and digital marketing strategies had a significant effect on the younger generation's interest in cultural events. The findings indicate that creative approaches to event presentation and optimal use of digital media are effective in increasing youth interest and participation.